Pemetaan potensi geothermal Seulawah Agam berdasarkan data DEMNAS dan Landsat 8 - Faisal Abdullah; Muhammad Yanis; Anshar Vahreza; Muhammad Isa; Nasrullah Zaini (Department of Physics, Sebelas Maret University, 2022)
Seulawah Agam is one of the volcanoes for geothermal energy development with an estimated 150 Mwe. At the exploration stage, thermal and multispectral image analysis is needed for surface temperature calculations, subsurface temperature modeling, and geothermal potential mapping of volcanoes. In this study, we used Landsat 8 and DEMNAS data to analyze the distribution of potential geothermal areas in the Seulawah Agam. Based on analysis of Fault Fracture Density (FFD) from DEMNAS, three classifications reflect the distance of the fault, namely low level (0 - 0.30 km/km2), medium (0.30-0.60 km/km2), and high (0.60-0.90 km/km2), where the distribution of geothermal potential is at medium and high-density levels. Meanwhile, the NDVI, NDWI data analysis shows dense vegetation areas on volcanoes and relatively rare in some manifestations. It can also be confirmed well by the high-temperature distribution in some craters between 34.63 C to 46.59 C. Based on observational data. It shows that DEMNAS and Landsat 8 data are very potential to be used as an initial method of analyzing the distribution of geothermal potential on the Seulawah Agam volcano.